Minimum Detectable Mass and Volume Fluxes During Magmatic Recharge at High Prominence Volcanoes: An Application to Erciyes Dağ Volcano (Turkey) - Males, Katie; Gottsmann, Jo (Frontiers in Earth Science, 2021)
Magma reservoir recharge is widely recognised as a precursor of eruptive activity. However, the causative relationships between reservoir rejuvenation and surface observables such as gravitational potential field changes and ground deformation are still poorly understood. At intermediate and silicic intra-plate volcanoes where crustal mechanical heterogeneity combined with high-prominence are expected to fundamentally affect the crustal stress and strain relationship, protracted period of repose and absence of monitoring data raise questions about the detectability of magma recharge. Here we report results from integrated geodetic forward modelling of ground displacements and gravity changes from reservoir recharge at Erciyes Dağ, a large prominence (∼2,800 m), yet poorly studied, stratovolcano of the Central Anatolian Volcanic Province in Turkey. The most recent eruption at ∼7000 BC, close proximity to the Kayseri Metropolitan Area and absence of dedicated volcano monitoring set a precedent to explore stealth magmatic processes at the volcano. Using finite element analysis we systematically explore the influence of subsurface mechanical heterogeneities and topography on surface deformation and gravity changes from magmatic recharge of Erciyes Dağ’s reservoir. We show that whilst crustal heterogeneity amplifies ground displacements and gravity variations, the volcano’s substantial prominence has the opposite effect. For generic reservoir pressure and density changes of 10 MPa and 10 kg m−3 predicted vertical displacements vary by a factor of 5 while residual gravity changes vary by a factor of 12 between models ignoring topography or mechanical heterogeneity and those that do not. We deduce reservoir volume and mass changes of order 10–3 km3 and 1010 kg, respectively, at the detectability limit of conventional surveying techniques at the volcano. Though dependent on model assumptions, all results indicate that magma recharge at Erciyes Dağ may go undetected at fluxes 1) sufficient to maintain an active reservoir containing eruptable magma and 2) similar to those reported for intermediate/silicic volcanoes with repose times of 100–1,000s of years (e.g., Parinacota) and persistently active mafic volcanoes such as Mt. Etna and Stromboli. Our findings may be utilised to inform integrated geodetic and gravimetric monitoring at Erciyes Dağ and other large prominence silicic volcanoes and could provide early insights into reservoir rejuvenation with implications for the development of disaster risk reduction initiatives.